Phonological processing, grammar and sentence comprehension in older and younger generations of Swedish children with cochlear implants. (February 2017) - Hansson, Kristina; Ibertsson, Tina; Asker-Árnason, Lena; Sahlén, Birgitta
Background and aims: Phonological processing skills measured by nonword repetition, are consistently found to be hampered in children with severe/profound hearing impairment and cochlear implants, compared to children with normal hearing. Many studies also find that grammar is affected. There are no studies exploring grammar in the Swedish population of children with cochlear implants. Documentation is also sparse regarding if and how language development in children with cochlear implants at the group level has changed over time with for example earlier implantation. The aim of the present study is to explore nonword repetition, grammatical production and sentence comprehension in an older generation of Swedish children with cochlear implants implanted during the 1990s and in a younger generation implanted after 2004. We also wanted to find out if and how nonword repetition is associated with grammatical production and comprehension in the two generations, taking the role of speech perception into consideration. Methods: Thirteen adolescents with severe/profound hearing impairment and unilateral cochlear implants, aged 11;9 to 19;1 at the time of testing (age at implant 2;5 to 11;11) and 16 children with severe/profound hearing impairment and cochlear implants, aged 5;3 to 8;0 (age at implant 0;7 to 5;6, ten bilateral) participated. All participants used oral communication. They were tested with nonword repetition and sentence comprehension tasks. Language samples for grammatical analysis were collected during a referential communication task. Transcriptions were analysed with respect to mean length of utterance and grammatical accuracy. Results: The two groups performed similar to each other and to reference data from much younger children with normal hearing and language development on nonword repetition. Both groups showed problems in grammatical accuracy. The majority of grammatical errors involved grammatical morphemes. All participants in the older group had significant problems with sentence comprehension, whereas variation was large in the younger group, some children performing at age level. In both groups, nonword repetition was associated with grammatical accuracy and in the younger group also with sentence comprehension. Conclusions: Phonological processing skills are significantly hampered in children with cochlear implants, with consequences for language processing and development. Their grammatical problems involve the use of grammatical morphemes, similar to what is found for hearing children with specific language impairment. In spite of early implantation, the results from the younger group indicate that this is still a group at risk for problems with language learning. Implications: Careful follow-up and support of language development in children with cochlear implants is crucial to identify children, whose problems are persistent. It is important for speech-language pathologists to take the interdependency of speech perception, phonological processing skills and other language skills into account.